The necessity of practical emergency cricothyroidotomy training during undergraduate medical education - Matthew MT. Carvey; Woong Kee Baek; Sarah Gluschitz; Robert Hage (Elsevier, 2020)
Background: A cricothyroidotomy is a procedure which creates a laryngeal opening. Medical students are told that this procedure is without major complications and simple to perform; however, professionals who have witnessed a laryngotomy include considerable hemorrhage and issues locating the correct insertion site in procedure preparation. Various laryngeal devices were analyzed, and determination of superiority was based on ease and success of insertion. Methods: Our study was limited to 30 healthcare professional volunteers and 3 devices: a scalpel, steak knife, and percutaneous cricothyroidotomy key-ring device (PCKD). Their task was to perform a laryngotomy within a set time period on a cadaver. 'Success or failure' was determined through dissection at a later date. Result: Among 30 volunteers, 21 successfully accessed the larynx. Success was highest with the steak knife and lowest with the PCKD, revealing device familiarity may be influential. Participants with previous clinical experience also had higher success, indicating practical experience may play a role in addition to anatomical knowledge. Conclusion: Cricothyroidotomy is a procedure mentioned in medical school, where theoretical knowledge is readily taught. Yet those who are deemed familiar with the anatomy is not reassuring. This presses the importance of medical curriculums implementing practical training, while simultaneously teaching the underlying anatomy and physiology. Trial registration: This study was approved by the St. George's University IRB, No. 06014. Keywords: Laryngotomy, Cricothyroidotomy, Emergency airway management, Medical education